The Influence of Interpersonal and Current Skills on The Performance of Village Owned Businesses in East Sumba Regency Through Good Corporate Governances - Gunawan, Fransiskus Xaverius Candra; Ali, Hapzi; Wihadanto, Ake (Dinasti Publisher, 2024)
Since 2017, the existence of 140 BUM Desa in East Sumba Regency has not shown good performance as pillars of the people's economy. This is reflected in the still high poverty rate and weak production sectors which can stimulate village economic growth. The aim of the research is to analyze how much influence interpersonal skills and current skills have on organizational performance through good corporate governance. The research method uses quantitative descriptive analysis techniques based on secondary and primary data obtained through questionnaires with a Likert scale approach. The results of the analysis of 144 respondents in 30 active BUM Desa using SEM analysis and smart pls 4 show that hypothesis H1 is accepted, namely that interpersonal skills have a positive and significant effect on the implementation of good corporate governance with a t-value of 6.678 and a p-value of 0.000. H2 is accepted, namely that current skills have a positive and significant effect on the implementation of good corporate governance with a t-value of 4.823 and a p-value of 0.000. H3 is accepted, namely the implementation of good corporate governance has a positive and significant effect on performance with a t-value of 3.986 and a p-value of 0.000. H4 is accepted, namely interpersonal skills have a positive and significant effect on performance with a t-value of 3.665 and a p-value of 0.000. H5 is rejected because it has a t-value of 0.345 which is smaller than 1.96 and a p-value of 0.730 with a significance of 5%, namely that current skills have no effect on performance. The results of this study recommend the need for concrete efforts to improve the interpersonal abilities and skills of current administrators. Apart from that, it is necessary to better implement the principles of transparency and accountability to improve the performance of BUM Desa by prioritizing the economic independence of local communities.